2022
DOI: 10.3390/ijerph19010511
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Analysis of the Shortened Version of the Spiritual Well-Being Scale on the Slovak Population (SWBS-Sk)

Abstract: This study was focused on verifying the factor structure of the shortened version of the Spiritual Well-Being Scale (SWBS) on a representative sample of adult Slovak citizens (N = 1018, 49% men, age 18–85 years, and mean age 46.2). The shortened version of the SWBS consists of 10 items divided into two subscales: religious well-being (RWB) and existential well-being (EWB). Results of confirmatory factor analysis (CFA) showed insufficient parameters of the full two-factor model due to three negatively formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Assessments asking spirituality/religiousness have been born in religious countries (Ferrell et al, 1995;Peterman et al, 2002;WHOQOL SRPB Group, 2006), and have focused on believers (Borges et al, 2021). In recent literatures searched on PubMed by keywords of "factor analysis or principal component analysis, spirituality/religion, and adolescent," there are a few studies investigating relationship between spiritual structures of healthy people and religiousness (Tavel et al, 2022;Vitorino et al, 2018). Employing the Shortened Version of the Spiritual Well-Being Scale, Tavel P, et al described religious respondents scored significantly higher on the two subscales of religious well-being and existential well-being (Tavel et al, 2022).…”
Section: Internal Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Assessments asking spirituality/religiousness have been born in religious countries (Ferrell et al, 1995;Peterman et al, 2002;WHOQOL SRPB Group, 2006), and have focused on believers (Borges et al, 2021). In recent literatures searched on PubMed by keywords of "factor analysis or principal component analysis, spirituality/religion, and adolescent," there are a few studies investigating relationship between spiritual structures of healthy people and religiousness (Tavel et al, 2022;Vitorino et al, 2018). Employing the Shortened Version of the Spiritual Well-Being Scale, Tavel P, et al described religious respondents scored significantly higher on the two subscales of religious well-being and existential well-being (Tavel et al, 2022).…”
Section: Internal Reliabilitymentioning
confidence: 99%
“…In recent literatures searched on PubMed by keywords of "factor analysis or principal component analysis, spirituality/religion, and adolescent," there are a few studies investigating relationship between spiritual structures of healthy people and religiousness (Tavel et al, 2022;Vitorino et al, 2018). Employing the Shortened Version of the Spiritual Well-Being Scale, Tavel P, et al described religious respondents scored significantly higher on the two subscales of religious well-being and existential well-being (Tavel et al, 2022). Vitorino LM et al, reported that participants with high religiousness had better outcomes as compared to those with low religiousness in the WHOQOL Psychological and Social Relationship, and Optimism (Vitorino et al, 2018).…”
Section: Internal Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Well-being was measured using the 3-item subscale of Existential Well-being from the Spiritual Well-Being Scale ( Bufford et al, 1991 ; Cotton et al, 2005 ; Malinakova et al, 2017 ; Tavel et al, 2022 ). The Existential Well-Being subscale is a measure of one’s sense of purpose in life.…”
Section: Methodsmentioning
confidence: 99%
“…The Spiritual Well-Being Scale (SWBS; Paloutzian and Ellison, 1982 ) is a self-report questionnaire that measures spiritual and life well-being. The Slovak version of SWBS was validated by Tavel et al (2022) . The SWBS consists of 20 items, from which either a summary score can be calculated or two subscales (religious well-being and existential well-being) can be derived.…”
Section: Methodsmentioning
confidence: 99%